OPTIMIZATION OF HEALTH TREATMENT FOR DEPRIANTS IN CORRECTIONAL INSTITUTIONS IN INDONESIA - Cahyoko Edi Tando; Umar Anwar (Polteknik Ilmu Pemasyarakatan, 2022)
Managing penitentiary (LAPAS) has its challenges because it has inmates who have different backgrounds, good management is needed and the right and accurate pattern or method to be able to realize an optimal LAPAS, especially in Indonesia. For this reason, this study will describe and analyze how and the obstacles that need to be watched out for in managing optimal prisons, then this study uses qualitative research methods in the form of a Systematic Literature Review or SLR using structured methods and patterns and the use of a reputable database well internationally. The results of this study indicate that to manage LAPAS in Indonesia, a strong legal umbrella is needed where the relevant government has to be able to provide good services to prison inmates. in the process of serving time in detention. Then the challenges that need to be anticipated are the psychological challenges faced by prison inmates during their detention period and if this does not get serious attention in managing LAPAS it will have an impact on other prison inmates.